(untitled) (The South East European Journal of Economics and Business, 2020)
This study aims to analyze the effect of financial deepening on economic growth, income inequality, and poverty rates in 73 countries during the period 1991-2015. Ordinary Least Squares (OLS) method with panel data regression is used in this study. This study also uses interaction of dummy variable and financial deepening indicators to measure the effect. The results indicate that financial deepening has positive effect on economic growth, but has negative effect on income inequality and poverty rates in 73 countries. Furthermore, financial deepening indicators have significant effect on economic growth in Advances Economies (AEs) and significant effect on income equality and poverty rates in Emerging Markets and Developing Economies (EMDEs). These findings show countries has to be selected in developing its financial sector as it either can have positive or negative effect.